Control of distension of varicose veins achieved by leg bandages, as used after injection sclerotherapy. Issue 6038 (25th September 1976) - Fentem, P H; Goddard, M; Gooden, B A; Yeung, C K
Abstract : A study was performed to determine whether the pressures routinely produced by bandaging for compression sclerotherapy of varicose veins are adequate to maintain the superfical veins almost empty of blood. The results suggest that well-applied bandages can provide sufficient support to combat the high distending pressures found in varicose veins. The large variation among different surgeons, however, indicates that any clinical assessment of compression sclerotherapy should include measurement of the pressure at which the bandages are applied.